Tuition Fees and Student Achievement - Evidence from a Differential Raise in Fees - Hans Fricke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This study analyses the effect of an increase in college costs on student achievement, particularly time-to-degree and performance. I exploit a unique policy at a Swiss university to identify and estimate the causal effect of an increase in tuition. Students faced an unexpected raise in tuition. This raise varied substantially across different students. The fees were increased by 81.7% for international students and by 20.2% for Swiss students. This variation allows me to follow a difference-in-differences strategy. I formally discuss identification with multiple treatments. I find at best modest effects of the increase on student achievement. Results suggest small positive anticipation effects on the probability to graduate and the credit accumulation for students at the end of their studies. These increased effort levels do not affect the grade average of the students. After the raise, the effects on the probability to graduate and the credit accumulation disappear. There is weak evidence of negative effects on credit accumulation and grades for students further away from graduation.
Keywords: I22; I23; C18; 330